THE EFFECT OF COMPANY SIZE AND PROFITABILITY ON SUSTAINABILITY REPORT DISCLOSURE WITH CORPORATE GOVERNANCE AS THE MODERATING VARIABLE - Asriani, Fauziah; Islahuddin, Islahuddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
The study examined the effect of company size and profitability on sustainability disclosure moderated by corporate governance. This quantitative research uses descriptive methods and multiple linear regression as the data analysis technique. The population of this research is the mining and basic material sector listed on IDX. Then, the purposive sampling method is used to obtain the sample. The data source is secondary data obtained from 2020-2021 sustainability reports and annual reports of mining and basic material sectors listed on the IDX. The results showed that company size and profitability affect sustainability disclosure, while corporate governance cannot moderate the effect of company size on sustainability disclosure. However, it can moderate the effect of profitability on sustainability disclosure.